High glucose‐induced excessive reactive oxygen species promote apoptosis through mitochondrial damage in rat cartilage endplate cells. Issue 9 (25th April 2018) - Jiang, Zengxin; Lu, Wei; Zeng, Qingmin; Li, Defang; Ding, Lei; Wu, Jingping
ABSTRACT: Diabetes mellitus (DM) is an important factor in intervertebral disc degeneration (IDD). Apoptosis of cartilage endplate (CEP) cells is one of the initiators of IDD. However, the effects of high glucose on CEP cells are still unknown. Therefore, we conducted the present study to evaluate the effects of high glucose on CEP cells and to identify the mechanisms of those effects. Rat CEP cells were isolated and cultured in 10% foetal bovine serum (FBS, normal control) or high‐glucose medium (10% FBS + 0.1 M glucose or 10% FBS + 0.2 M glucose, experimental conditions) for 1 or 3 days. In addition, CEP cells were treated with 0.2 M glucose for 3 days in the presence or absence of alpha‐lipoic acid (ALA, 0.15 M). Flow cytometry was performed to identify and quantify the degree of apoptosis. The expression of reactive oxygen species (ROS) was assessed by flow cytometry, and mitochondrial damage (mitochondrial membrane potential) was assessed by fluorescence microscopy. Furthermore, the expression levels of cleaved caspase‐3, cleaved caspase‐9, Bcl‐2, Bax, and cytochrome c were evaluated by Western blotting. High glucose significantly increased apoptosis and ROS accumulation in CEP cells in a dose‐ and time‐dependent manner. Meanwhile, a disrupted mitochondrial membrane potential was detected in rat CEP cells cultured in the two high glucose concentrations. Incubating in high glucose enhanced the expression levels of cleaved caspase‐3, cleaved caspase‐9, Bax, and cytochrome c but decreased the level of the anti‐apoptotic protein Bcl‐2. ALA inhibited the expression of cleaved caspase‐3, cleaved caspase‐9, Bax, and cytochrome c but enhanced the expression of Bcl‐2. ALA also prevented disruption of the mitochondrial membrane potential in CEP cells. This study demonstrates that high glucose‐induced excessive reactive oxygen species promote mitochondrial damage, thus causing apoptosis in rat CEP cells in a dose‐ and time‐dependent manner. ALA could prevent mitochondrial damage and apoptosis caused by high glucose in CEP cells. The results suggest that appropriate blood glucose control may be the key to preventing IDD in diabetic patients. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2476–2483, 2018.